The effectiveness of perceived personalisation on personalised advertising on social media - Zhou, Jiahui (2022)
Social networking is essential in the Web 2.0 era. Marketers use social media for advertising and branding. Social media advertising will reach 116 billion dollars in 2021, according to forecasts. Personal relevance increases consumer attention and response. Online behavioural advertising (OBA) tailors adverts to each user's network activities. While it benefits advertisers, it has several issues. When confronted with personalised advertising, customers assess the advantages (more relevant information) against the costs (privacy issues). Businesses are using personalised advertising to enhance profits. Will consumers be more open to customised adverts or ignore them out of worry for their data? Based on the privacy calculus theory and the use and gratification theory, this study tries to examines how perceived personalisation of OBA affects consumers’ click intention. Investigating the effect of perceived personalisation on the intention to click on online behavioural advertising by analysing five mediating variables: perceived value (informativeness and entertainment), perceived risk (intrusiveness and privacy risk), and personal relevance. This study uses a scenario-based questionnaire with two groups to assess perceived personalization's influence on click intention in two usage motivation situations (purchase-oriented and entertainment-oriented). The survey results show that perceived personalisation influences consumers' click intention via its personal relevance, including the mediating effect of perceived value. When consumers are aware that personalisation involves the use of their personal information, they will assess the perceived risk of advertising material. However, people's estimation of the likelihood of privacy issues has no effect on their intent to click on OBA. Compared to the purchase motivation scenario, in the entertainment scenario, perceived personalisation has no impact on perceived privacy risk and perceived intrusiveness. This means that individuals take privacy 2 risk more seriously due to their financial rewards in the purchase motivation scenario. According to the results, people agree that OBA brought risks to their privacy, yet they do not think it actually threats their private rights. In comparison to other privacy concerns, the perception of intrusiveness induced by OBA clicks is minimal. So the effect of perceived personalisation on click intention of OBA is accomplished through perceived value. The finding and conclusions also shed more light on personalised advertising for companies and brands.